Estudo do transporte de sedimentos na bacia hidrográfica do rio Jordão – UPGRH-PN 1 - Peixoto, Rodrigo de Almeida Oliveira (2019)
The understanding of the sediment flow is fundamental for the adequate management of the water resources. The lack of planning for land use and occupation marked by irrational anthropogenic actions directly influences the sediment transport in river basins throughout the national territory. The intensification of the transport of sediments causes several problems that interfere in the normal conditions of balance of the environment, damaging environmental, economic and social aspects. In this context, the research aims to study sediment transport in the river Jordão basin, which belongs to the Water Resources Planning and Management Unit - Alto Rio Paranaíba 1 (UPGRH-PN1), in order to understand the the flow of solid particles to contribute to studies related to silting reservoirs, planning and management of the region's water resources. For this purpose, four sampling stations were established, fourteen campaigns were carried out for flow measurements and collection of water and sediments for the analysis of suspended and bed sediments during dry and rainy seasons from August 2017 to December 2018. With this it was possible to estimate the solid discharge by different methods; characterize the sediment granulometry and the hydraulic and geometric aspects of the studied sections; build the key curves of liquid and solid flow; simulate sediment transport from the computational tool (HEC-RAS); and to analyze the factors that influence sediment transport in the river basin of the Jordão River. The results showed that sediment concentrations and discharges showed variations between the seasons and sampling periods. In the rainy season the values of discharges and concentrations were higher than in the dry season. In the rainy season the values of discharges and concentrations were higher than in the dry season. The sediment and total sediment key curves obtained for each season and for the united data of all seasons showed good correlations. The simulations indicated temporal and spatial trends of erosion and sediment deposition along the river. In this way, it was possible to better understand sediment transport transport in the Jordão River, and to provide subsidies for decision-making by the competent sectors, in order to improve the management of water resources in the river basin.